(untitled) (Research, Society and Development, 2022)
Urinary tract infections (UTIs) are inflammatory pathologies resulting from the multiplication of microorganisms in the urinary tract. The risk group includes pregnant women, due to physiological changes caused by pregnancy, and such conditions are related to a greater risk of maternal-fetal complications. Treatment is based on the most likely etiology and should consider microbial sensitivity to antimicrobials, given the increasing emergence of resistance. Given the need to monitor the pathogenic epidemiology and its susceptibility, the study aims to determine the etiological and susceptibility profile of the microorganisms that cause UTI in pregnant women in the city of Palmas, Brazil. This is a descriptive observational study, based on the exploration of data made available by the clinical analysis laboratory of the Dona Regina Hospital and Maternity, located in Palmas. Urine culture and antibiogram results of pregnant women attended over a 12-month period (July/2021 - June/2022) were evaluated. The project was registered on Plataforma Brasil, for appreciation and analysis by the CEP/UFT, thus being adequate to the current regulations. It was found that the etiology of infections was predominantly associated with Escherichia coli (34.75%) and Enterococcus faecalis (23.73%). The drugs with the highest resistance rate were ampicillin (53.47%) and sulfamethoxazole with trimethoprim (41.56%); nitrofurantoin had the lowest rate (3.39%). It is concluded that the etiological profile corresponds to bacteria colonizing the gastrointestinal tract, which have some degree of resistance, especially to ampicillin, and have considerable sensitivity to nitrofurantoin.